Identification, variabilité et ëcologie d'Ophelia rathkei McIntosh, espèce nouvelle pour les côtes Françaises - Chassé, C.; Picard, J. (Cahiers de Biologie Marine, 1968)
Summary: The authors indicate the presence of an annelid polychete (family Opheliidae) long about 1 cm (-1/3 inch), in the sands of Roscoff (Brittany). The amplitude of variations concerning its morphological characters allows us to identify it with Ophelia rathkei McIntosh 1908 as well as with Ophelia remani [sic] Augener 1939 and Ophelia cluthensis McGuire 1935 which are known from the British Isles and from Germany; these polychetes form thus one single species (with 8 to 10 pairs of gills), living in well oxygenized, homometrical fine sands (median from 200 to 300) of neap-tide oscillation zone. Sands with this Ophelia finds intermittend [sic] between Ophelia bicornis (sands in the upper part) and those containing Travesia forbesi and Ophelia neglecta populations (in the lower part).
World Polychaeta Database (WPolyD)